Kwestia Malwinów/Falklandów w polityce zagranicznej prezydenta Carlosa Menema - Kita, Agnieszka (Acta Universitatis Lodziensis. Folia Historica, 2014)
Argentine-British Falklands Islands war in 1982 was the apogee of the conflict which was stretching already since the 30s of XIXth century. The war was broke out by the military junta, which was ruling the country in the years 1976–1983 and was ended with Argentina’s defeat and with the end of rule of the generals. However, despite of the defeat and humiliation, the next governments (already democratic) did not abandon their plans to get back the islands. It has to took place in peaceful negotiations, to which it was necessary to restore mutual bilateral relations between Buenos Aires and London. Partially was this plan realised by Carlos Menem’s Cabinet, the second, after 1983, democratically elected government. During his double presidential tenure (1989–1999) Carlos Saúl Menem has achieved measurable successes in the renewal of Argentine- British relations. He managed not only restore formal diplomatic relations, but also he renewed the exchange of trade and political cooperation with United Kingdom. Menem was also first since long time Argentine leader, who has visited the Great Britain. Thank to intense, but without real results procedures of the Foreign Minister Guido Di Tello, Menem’s administration showed, that in the Falklands Islands issue is focused on dialogue and peaceful resolution of the dispute. Despite the fact that under the leadership of a new president, a greater emphasis was placed on bilateral talks, they did not try to avoid mediation of third countries (such as United States or Spain). The normalization of mutual relations did not mean that the Great Britan resigned from wielding the supervision over Falkland Islands.